Adsorpsi Paraquat dan Sifat Tanah pada Tiga Subgrup Tanah Akibat Pemberian Amelioran - Rija Sudirja; Mahfud Arifin; Benny Joy (Fakultas Pertanian Universitas Padjadjaran, 2015)
ABSTRACTParaquat adsorption and Soil Properties on Three Soil Subgroups Due to Ameliorant ApplicationParaquat (Bipyridylium biclorida) is known as a highly toxic herbicide and quite widely used by the farmers. The material can be adsorbed by soil colloids and can contaminate soil and water. The study aimed to determine the ability of three of soil subgroups of different orders (Typic Hapludult, Typic Hapludand,and Chromic Endoaquert) to adsorb paraquat, finding the best kind of ameliorant in reducing residues, and studying its effect on corn crops. The study was conducted in two stages, namely (1) to test the maximum adsorption capacity of paraquat on the three of soil subgroups based on the Langmuir equation, and (ii) to study the influence of the type and ameliorant dose on three soil subgroups saturated with paraquat. Methods used were completely randomized design experiment nested models. The results of laboratory experiments showed that the topsoil layer of Typic Hapludands was dominated by halloysite and little amorphous clay minerals. While predominantly Typic Hapludult was dominated by kaolinite and little smectite. Chromic Endoaquert contained little kaolinite and was dominated by smectite. Saturation points in all three soil subgroups were 1.883 cmol kg-1, 20.833 cmol kg-1, and 9.346 cmol kg-1 paraquat, respectively. The type and dose of each ameliorant signifancty affected paraquat adsorption capacity, soil pH and electrical conductivity in all three soil subgroups, except for paraquat adsorption capacity and pH which were not affected in Typic Hapludults. The highest dose of activated charcoal adsorbed paraquat markedly higher compared with other treatments on Typic Hapludands, whereas Chromic Endoaquerts activated charcoal had the same effect with the zeolite, but higher than straw and control. Furthermore, on Typic Hapludults ameliorant did not significantly affect the adsorption capacity of paraquat, except when compared with controls.Keywords: Paraquat, soil subgroups, adsorption, ameliorant.ABSTRAKParaquat (Bipyridylium biclorida) dikenal sebagai herbisida yang sangat toksik dan pengunaannya cukup luas di kalangan petani. Bahan ini dapat diadsorpsi oleh koloid tanah dan dapat mencemari tanah dan air. Penelitian ini bertujuan untuk mengetahui kemampuan tiga subgrup tanah berlainan ordo (Hapludult Tipik, Hapludand Tipik, dan Endoequert Kromik) mengadsorpsi paraquat, menemukan jenis amelioran yang paling baik dalam menekan residu paraquat, serta mempelajari pengaruhnya terhadap hasil tanaman jagung. Penelitian dilakukan dalam dua tahap, yaitu (1) Uji kapasitas adsorpsi maksimum paraquat pada tiga subgrup tanah berdasarkan persamaan Langmuir, dan (2) pengaruh jenis dan dosis amelioran pada tiga subgrup tanah terjenuhi paraquat terhadap adsorpsi, pH, dan daya hantar listrik. Metode yang digunakan Rancangan Acak Lengkap model percobaan Tersarang. Hasil percobaan di laboratorium menunjukkan titik jenuh paraquat pada ketiga subgrup tanah tersebut masing-masing sebesar 1,883 cmol kg-1, 20,833 cmol kg-1, dan 9,346 cmol kg-1. Jenis dan dosis amelioran masing-masing berpengaruh nyata terhadap kapasitas adsorpsi paraquat, pH tanah dan daya hantar listrik pada ketiga subgrup tanah, kecuali kapasitas adsorpsi paraquat dan pH tidak dipengaruhi pada Hapludult Tipik. Arang aktif dosis 20% media tanah mampu mengadsorpsi paraquat nyata lebih tinggi dibandingkan dengan perlakuan lainnya pada Hapludand Tipik, sedangkan pada Endoaquert Kromik, arang aktif memiliki pengaruh yang sama dengan zeolit, tetapi lebih tinggi dari jerami dan kontrol.